Sapta-pāṭhī Śrīśiva-mahimna-stotram - Puṣpadanta, Ācārya ca. 8./9. Jh. (Kāśı̄ saṃskṛta granthamālā / Bauddhanyāyavibhāga, 1983)
Classical hymn to Śiva, Hindu deity; includes Śaktimahimnahstotra, hymn to Tripurasundarī, Hindu deity, traditionally ascribed to Durvāsā